ANALISA PROSES PRODUKSI KAIN SARUNG DI PT. P DENGAN MELAKUKAN PENDEKATAN LEAN MANUFACTURING - Ariq Rifqi Zaini (2021)
In this era of world globalization and free trade as it is now, the industry in Indonesia has experienced significant development. According to the book Analysis of Indonesia's Industrial Development Edition I-2020, the textile industry experienced an increase from 2017 to 2019. This triggered increasingly fierce industrial competition where good services were needed so that the company's name was maintained in the field. PT. P is one of the many manufacturing companies that produce sarongs. Based on observations and the seven waste questionnaires, there is still waste that has the potential to cause losses, therefore it is necessary to improve activities that have the potential to cause waste. The purpose of this study is to provide recommendations for improvement to minimize waste to create effectiveness and efficiency in the production system that is run and to see a comparison of the implementation results through the ProModel software. The results show that there are 3 biggest wastes, namely transportation, defective products, and waste of motion. Methodologies in problem solving are Value Stream Mapping, Value Stream Analysis Tools (VALSAT), Failure Mode Effect Analysis (FMEA), and Fault Tree Analysis (FTA). From the results of data processing, it was found that the lead time decreased by 8.82 minutes, the effect of layout changes, and an average output increase of 342 beams (18.1%) in 1 month which is known through simulation."